Implications of the global growth slowdown for rural poverty - Laborde Debucquet, David; Martin, Will (Wiley, 2018)
Unfortunately, projected growth rates have fallen in recent years; this paper examines the impact of this slowdown on the poor, particularly the rural poor. It first uses a global model to assess the impacts of lower productivity on key price and income variables. It then uses microsimulation models for almost 300,000 households to assess the impacts on their real incomes. Although poverty rates overall are projected to fall substantially, the poorest countries see the greatest slowdown in poverty reduction, with over 5 percent of their population projected to remain below the poverty line. In addition, poverty rates will remain alarmingly high in many countries. By 2030, average extreme poverty in rural areas is now projected at about 7.5 percent, rather than previous estimates of 7.1 percent.